Innovative Exploration: Strategies of Islamic Boarding School Leaders in Addressing Radicalism through Educational Transformation - Rafik, Ainur; Nurchayati, Siti (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2024)
This research aims to analyze the understanding of radicalism in Islamic boarding schools and the patterns of Islamic boarding school leaders in countering radicalism. This research uses a qualitative case study type approach. The data collection techniques are observation, documentation and interviews. Data analysis uses the Milles and Huberman model: data collection, data reduction, data presentation and conclusions. The research results show that 1) radicalism can be understood in the aspect of a deep understanding of religion and actions in the name of shallow religion, 2) Islamic boarding schools' efforts to ward off radicalism include instilling religious values based on the Qur'an and As-Sunnah, the Islamic principles of rahmatan lil'aalamin, and enlightenment of student by combining the concept of ijtihad fikriyah. They also encourage attitudes of tolerance, tasamuh, and love of the country. In the social sector, Islamic boarding schools interact directly with the community, holding routine activities such as weekly recitations and deliberations to resolve problems. They also practice mutual understanding and respect for differences. In culture, Islamic boarding schools teach an understanding of cultural diversity and mutual respect for differences. The implication is to strengthen the perspective of Kyai and Islamic boarding school managers towards radicalism with a deep understanding and rejection of violence in the name of religion.